2019
DOI: 10.1016/j.phytochem.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of Bowman-Birk and Kunitz isoinhibitors from the seeds of Rhynchosia sublobata (Schumach.) Meikle, a wild relative of pigeonpea

Abstract: Rhynchosia sublobata, a wild relative of pigeonpea, possesses defensive proteinase/protease inhibitors (PIs). Characterization of trypsin specific PIs (RsPI) separated from seeds by column chromatography using 2-D gel electrophoresis and Edman degradation method identified R. sublobata possessed both Bowman-Birk isoinhibitors (RsBBI) and Kunitz isoinhibitors (RsKI). A quick method was developed to separate RsBBI and RsKI from RsPI based on their differential solubility in TCA and acetate buffer. N-terminus seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…As for GASP-1 and GASP-2, we measured inhibitor/trypsin dissociation K i values of 220 and 290 nM for mGASP-1/Ku 2-2 and mGASP-2/Ku 2-1 , respectively. K i values are of the same order of magnitude as those obtained for the two recombinant mGASP proteins or several antiproteases containing a Ku domain [28,29]. Kinetic analyzes showed that the mGASP-1/Ku 2-2 chimeric protein exhibits a competitive-type inhibition mechanism similar to that described for GASP-2.…”
Section: Construction Expression and Purification Of The Two Recombsupporting
confidence: 64%
“…As for GASP-1 and GASP-2, we measured inhibitor/trypsin dissociation K i values of 220 and 290 nM for mGASP-1/Ku 2-2 and mGASP-2/Ku 2-1 , respectively. K i values are of the same order of magnitude as those obtained for the two recombinant mGASP proteins or several antiproteases containing a Ku domain [28,29]. Kinetic analyzes showed that the mGASP-1/Ku 2-2 chimeric protein exhibits a competitive-type inhibition mechanism similar to that described for GASP-2.…”
Section: Construction Expression and Purification Of The Two Recombsupporting
confidence: 64%
“…Besides, the self-association of BBIs not only provides stability, but also important in molecular packing as a seed storage protein (Hogg, 2003;Kumar et al, 2015). All the isoinhibitors visualized on one and two-dimensional gel electrophoresis conferred resistance against trypsin and chymotrypsin digestion (Figures 2C,D,F,G; Prasad et al, 2010a;Swathi et al, 2016;Mohanraj et al, 2019). The prominent TI activity was evidenced through wider protective zones against trypsin as compared to chymotrypsin during gelatin in-gel activity staining (Figure 2F).…”
Section: Biochemical and Biophysical Characterization Of Macromoleculmentioning
confidence: 99%
“…The protease activity was identified by observing the formation rate of p-nitroanilide from BAPNA or GLUPHEPA (1 mM) at 410 nm using UV-visible spectrophotometer (UV-1700, Shimadzu, Japan) as described in Mohanraj et al (2019). The p-nitroanilide molar extinction coefficient (M −1 cm −1 ) is corresponding to 8800 at 410 nm.…”
Section: Assay Of Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TI from other sources including fish roe (Klomklao et al, 2016;Ustadi et al, 2005), chicken plasma (Rawdkuen, Benjakul, Visessanguan, & Lanier, 2005), mung bean (Klomklao, Benjakul, Kishimura, & Chaijan, 2011), and the seed of Rhynchosia sublobata (Schumach.) Meikle (Mohanraj et al, 2019) were also isolated, purified as well as characterized. Recently, protease inhibitors present in duck albumen has been proven to exhibit higher inhibitory activity than hen albumen (Quan & Benjakul, 2018a).…”
mentioning
confidence: 99%